Предмет: Алгебра,
автор: мама1433
(x+1)(x^2-x+1)-x(x+2)(x-2)=3
Ответы
Автор ответа:
0
х*3 + 1 - х( х*2 - 4 ) =3
х*3 + 1 - х*3 + 4х = 3
4х = 2
х = 2 / 4
х = 1/2
х*3 + 1 - х*3 + 4х = 3
4х = 2
х = 2 / 4
х = 1/2
Автор ответа:
0
1)(x+1)(x^2-x+1)=x^3-x^2-x+x^2-x+1
2)x(x^2-4)=x^3-4x
Теперь отнимаем
x^3-x^2-x+x^2-x+1-x^3+4x=3
X^3 и x^2 сокращает
Получается
2x+1+4x=3
X=1/3
Похожие вопросы
Предмет: Геометрия,
автор: liliputt21
Предмет: Українська мова,
автор: marinaaromij05
Предмет: Биология,
автор: TN188
Предмет: Математика,
автор: Sara2527